Assessment of Fertility Status in the Male Sumatran Rhino at the Sumateran Rhino Sanctuary, Way Kambas National Park, Lampung - MUHAMMAD AGIL; IMAN SUPRIATNA; BAMBANG PURWANTARA; DEDI CANDRA (Bogor Agricultural University, Indonesia, 2008)
Sumatran rhino is the most endangered rhino species. Its population is estimated less than 300 individuals remaining in the wild with highly declining rate to 50% in the last 15 years. The number of male rhinoceroses in the captivity are very few, therefore the assessment of its fertility is very important in order to support the breeding success since the captive breeding success is very poor. The objectives of this study were (i) to determine the male reproductive status, (ii) to establish a reliable semen collection method, and (iii) to assess semen parameters of the fresh collected sample. Three methods of semen collection were examined to determine its fertilizing potential, i.e. (i) stimulated combination of artificial vagina (AV), penile massage (PM) and accessory gland massage (AGM); (ii) AV and PM; and (iii) only with PM. The first method gave the best result with an ejaculation success of 85.71% (6/7, n = 7). The second and third methods obtained an ejaculation success rate of 50% (2/4, n = 4)) and 25% (1/4, n = 4), respectively. The collected ejaculates had a volume of 1.2-12.4 ml with whitish to cream turbid colour and pH 6.90-6.99. Sperm concentration was (143-333) x 103 sperm/ml. The quality of the sperm was low with only approximately 1% of them moved forward slowly. Approximately 80% of the spermatozoa were immature (prox. cytoplasmic droplet) with head (macro-, microcephalic) and tail abnormalities (broken tail). Semen quality increased after several collections and the amount of immature sperm decreased up to 5%. Electroejaculation procedure could produce 34 ml semen, but no sperm was found in the ejaculate. Hence, the combination of AV, PM, and AGM could get higher volume of ejaculate compared to other methods, but sperm concentration was better obtained using AV and PM only. Repeated semen collection increased semen quality, although the male has low fertilizing capacity due to low sperm concentration (oligozoospermia) and small volume of the ejaculate (oligospermia). Key words: Sumatran rhino, semen, sperms, collection